The productive capacity and environment: evidence from OECD countries - Oluç, İhsan; Ben Jebli, Mehdi; Can, Muhlis; Güzel, İhsan; Brusselaers, Jan (SPRINGER HEIDELBERG, 2022)
Environmental degradation is one of the most important and vital issues of today. In this context, many researchers are testing the environmental impact of diferent indicators. Many economic parameters afect environmental degradation. At the forefront of these parameters is the productive economic structures of the countries. For the frst time in the literature, the present paper discusses the dynamic relationship between carbon dioxide (CO2) emissions, economic growth, and the productive capacity index (PCI) for a panel of 38 organization for economic co-operation and development (OECD) countries spanning the period 2000–2018. In this context, the PCI serves as a measure of the productive economic structure of a country. This empirical study applies panel cointegration techniques to reveal that the series are cointegrated in the long-run. In addition, the pooled mean group-panel autoregressive distributive lag (PMG-ARDL) approach is employed to estimate long-run coeffcients. These coefcients confrm the environmental Kuznets curve hypothesis. Finally, the empirical fndings confrm that improved productive capacity decreases environmental degradation. This results in important policy recommendations for involved governmental and private stakeholders.
Keywords: Environmental degradation; Knowledge economy; Economic complexity; Productive capacity; Greenhouse gasses; OECD economies